Contact mechanical behaviors of radial metal seal for the interval control valve in intelligent well: Modeling and theoretical study. Issue 4 (22nd December 2019) - Yang, Yiwei; Zhu, Hongwu; He, Dongsheng; Du, Changcheng; Xu, Liangbin; He, Yufa; Zheng, Yan; Ye, Zhewei
Abstract: Intelligent wells equipped with the interval control valve (ICV), which have the potential applications to significantly improve oil production or control the water production of wells and fields, are more and more widely utilized in the oilfields. The radial metal seal of an ICV is intended to isolate the flow of produced fluids between the casing annulus and the well tubing. The contact mechanical behaviors of the radial metal seal are essential to the structural design and reliability of ICVs in the intelligent well. In this paper, the two‐dimensional axisymmetric assembly of the radial metal seal and the closure member is abstracted as a combination of interference fit model and cantilever beam model. Based on that, the related theoretical model, between the radial metal seal's contact stress and its independent variables, has been derived. Next, numerically simulations of contact stress between the radial metal seal and the closure member for different independent variables are conducted by the finite element method (FEM) to validate the theoretical model. It is found that the mean absolute value of relative error between the numerical and theoretical results of the contact stress is approximately 10%. Additionally, the structural parameters of the radial metal seal are proposed with the absolute value of relative error <10%. Furthermore, the value of the contact stress based on the cantilever beam model can be used to calculate an approximation theoretical solution. In summary, the proposed theoretical model provides a foundation for the design, improvement, and selection of radial metal seal under the known oilfield conditions. Abstract : The two‐dimensional axisymmetric assembly of the radial metal seal and the closure member is abstracted as a combination of interference fit model and cantilever beam model. The related theoretical model between the radial metal seal's contact stress and its independent variables has been derived. Numerically simulations of contact stress between the radial metal seal and the closure member for different independent variables are conducted by FEM to validate the theoretical model.